A Study of the Satirical Consciousness of Dr. Ajay Anuragi in Contemporary Hindi Satirical Literature: समकालीन हिंदी व्यंग्य साहित्य में डॉ. अजय अनुरागी की व्यंग्य चेतना का अध्ययन - Agarwal, Anil; Saini, Sumitra (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
On the vast canvas of contemporary Hindi satirical literature, the writings of Dr. Ajay Anuragi emerge as a powerful intellectual consciousness that exposes the inherent contradictions, inconsistencies, and deep ironies present within Indian society with remarkable clarity. Connecting the classical tradition of satire with modern contexts, he has targeted the immorality and stagnation prevalent in politics, administration, religion, and everyday public life through his sharp and perceptive vision. The most significant feature of his literature is that humor in his works is not merely a means of superficial entertainment; rather, it is shaped through a rare synthesis of compassion, anger, and sharp criticism, which not only provides immediate pleasure to the reader but also compels them to confront harsh social realities. Through his satire, Dr. Anuragi has vividly portrayed the roots of corruption, the grotesque form of power-hungry politics, administrative inefficiency, and religious hypocrisy, while also offering a sensitive analysis of their underlying causes. His literary expression possesses a sharpness that highlights the moral decline of society and spreads a sense of awareness among readers, encouraging them to move beyond the acceptance of the status quo and think in the direction of change. In essence, the satire of Dr. Ajay Anuragi is not merely a critical literary form but a meaningful endeavor to awaken social consciousness. In the developmental journey of contemporary Hindi satire, his contribution stands as an important and indispensable link, playing a significant role in providing society with a vigilant and thoughtful perspective along with literary significance. Abstract in Hindi Language: समकालीन हिंदी व्यंग्य साहित्य के विस्तृत फलक पर डॉ. अजय अनुरागी का लेखन एक ऐसी सशक्त वैचारिक चेतना के रूप में उभरता है, जो भारतीय समाज की अंतर्निहित विसंगतियों, विडंबनाओं और गहरे अंतर्विरोधों को पूरी नग्नता के साथ उद्घाटित करता है। व्यंग्य की शास्त्रीय परंपरा को आधुनिक संदर्भों से जोड़ते हुए उन्होंने राजनीति, प्रशासन, धर्म और आम जनजीवन में व्याप्त अनैतिकता और जड़ता को अपनी तीक्ष्ण दृष्टि का लक्ष्य बनाया है। उनके साहित्य की सबसे बड़ी विशेषता यह है कि वहाँ हास्य केवल सतही मनोरंजन का साधन नहीं है, बल्कि वह करुणा, आक्रोश और प्रहारात्मकता के एक ऐसे दुर्लभ समन्वय से निर्मित है, जो पाठक को तात्कालिक आनंद देने के साथ-साथ कठोर सामाजिक यथार्थ से साक्षात्कार करने पर विवश कर देता है। डॉ. अनुरागी ने अपने व्यंग्य के माध्यम से भ्रष्टाचार की जड़ों, सत्ता-लोलुपता के वीभत्स स्वरूप, प्रशासनिक शिथिलता और धार्मिक आडंबरों पर न केवल सजीव चित्रण किया है, बल्कि उनके मूल कारणों की मार्मिक मीमांसा भी की है। उनके शब्द शिल्प में वह धार है जो समाज के नैतिक पतन को रेखांकित करते हुए पाठकों के भीतर एक व्यापक जागरूकता का संचार करती है और उन्हें यथास्थितिवाद को त्यागकर परिवर्तन की दिशा में सोचने हेतु प्रेरित करती है। वास्तव में, डॉ. अजय अनुरागी का व्यंग्य केवल एक आलोचनात्मक विधा मात्र नहीं है, बल्कि वह सामाजिक चेतना को जाग्रत करने का एक सार्थक अनुष्ठान है। समकालीन हिंदी व्यंग्य की विकास-यात्रा में उनका कृतित्व एक महत्वपूर्ण और अनिवार्य कड़ी के रूप में स्थापित होता है, जो साहित्यिक सार्थकता के साथ-साथ समाज को एक सजग और विवेकशील दृष्टि प्रदान करने में महती भूमिका निभाता है। Keywords: डॉ. अजय अनुरागी, समकालीन व्यंग्य, साहित्यिक दृष्टि, चेतना, समाज, राजनीति, प्रशासन, धार्मिक जीवन, सामाजिक यथार्थ।